Educational mobile game for learning English words. Issue 1 (November 2020) - Ng, B K; Suaib, N M; Sihes, A J; Ali, A; Shah, Z A
Abstract: English is a second language in Malaysia and English language skills are vital for Malaysians. Mobile technologies such as mobile phone can be a great tool for educational purposes since it can increase students' engagement and is a popular tool for interactive digital media. This paper discusses the development of an educational mobile game called EWORD for learning English words, for primary school kids. There were four phases involved; preliminary analysis, game design, game development and game evaluation. In the first phase, the fundamental knowledge of English words and vocabulary, English language learning methods in Malaysia, traditional learning methods, and educational mobile game were studied to acquire adequate information about the requirements for educational mobile game. User Interface (UI), gameplay, and game mechanics were designed in the second phase, while the mobile game prototype was developed in the third phase. In the fourth phase, the evaluation was conducted to evaluate the usability of the educational mobile game prototype. Based on the results, the educational mobile game helps in boosting the learnability of English words among students and is capable to increase student engagement.